2013
DOI: 10.1017/sjp.2013.97
|View full text |Cite
|
Sign up to set email alerts
|

When the Care Ends: Emotional State of Spanish Bereaved Caregivers of Persons with Dementia

Abstract: Several researchers have found that caring for relatives with dementia has negative consequences on the caregiver’s physical and emotional health during the caregiving period. However, less attention has been paid to caregiver´s emotional state after the patient´s death. The aims of this study are 1) to evaluate the emotional state of the Spanish former caregivers after the care recipient death, and 2) to analyze the patient’s death circumstances and their influence in the current emotional state of caregivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
(42 reference statements)
4
19
1
1
Order By: Relevance
“…Being able to say goodbye to the person with dementia before they died had a positive effect on carer post-care emotional state, as has been noted previously (Crespo et al , 2013). Carers expressed relief the care journey had ended, not for their own sakes, but for the person with dementia, relieved that their suffering had ended and their dignity could be restored, as previously found (Aneshensel et al , 2004).…”
Section: Discussionsupporting
confidence: 74%
“…Being able to say goodbye to the person with dementia before they died had a positive effect on carer post-care emotional state, as has been noted previously (Crespo et al , 2013). Carers expressed relief the care journey had ended, not for their own sakes, but for the person with dementia, relieved that their suffering had ended and their dignity could be restored, as previously found (Aneshensel et al , 2004).…”
Section: Discussionsupporting
confidence: 74%
“…Emotionally engaging (ie, feeling connected to) and consciously "letting go" or loosening the bond on the physical relationship with PwD while reinforcing relationships with others. 30,31,39,47,65,67,68,78 Fulfilling final perceived obligations (eg, being present at time of death) saying goodbye and express sentiments (eg, gratitude, forgiveness, and love) 45,67,30,81 Acting as a surrogate for PwD (whom were unable to complete tasks themselves) to participate in rituals, activities and saying goodbye, celebrating life completion, and closure in line with their values 78,88 Planning and celebrating spiritual beliefs brought peace and structure in line with personal and PwD's values 31,40,67,88,98 Abbreviations: CG, caregiver; EOL, end of life; HCP, health-care provider; PwD, persons with dementia.…”
Section: Promoting Problem-and Emotion-based Coping Skillsmentioning
confidence: 99%
“…Some studies reveal a decrease in depressive symptoms as bereavement progresses [ 16 , 24 ], while others note an increase in depressive symptoms [ 25 ]. On the other hand, a Spanish study conducted by Crespo, Piccini and Bernaldo-de-Quiros [ 26 ] found that among their sample of spousal and adult children caregivers, most (over 65%) did not develop any significant depressive symptoms over the study’s three year period. It is evident that dementia caregivers do not have uniform emotional responses to bereavement.…”
Section: Introductionmentioning
confidence: 95%